Accounting Changes: Successful Versus Unsuccessful Firms. - Lilien, Steven; Mellman, Martin; Pastena, Victor (The Accounting Review, 1988)
Abstract ABSTRACT: Both descriptive and statistical analyses of the pattern of accounting changes of successful and unsuccessful firms Indicate that unsuccessful firms am more likely than successful firms to make accounting changes that increase Income. Sample firms are matched by Industry membership to control for macroeconomic factors. Success is measured by the total market return to shareholders over a ten-year period. The empirical findings are consistent with the assertion that managers can modify reported Income through judicious accounting changes.